Analisis Visual dan Karakteristik Klub Sepakbola Liga Inggris Berdasarkan Pola Permainan Menggunakan K-Means Clustering - Yudhianto, Rachmat Bintang; Yusuf, Fajar Athallah; Fitrianto, Anwar; Jumansyah, L.M. Risman Dwi (Jurnal Informatika Universitas Pamulang, 2024)
This research aimed to analyze and cluster football teams in the English Premier League (EPL) for the 2023/2024 season based on their playing characteristics using K-Means clustering. Understanding the playing styles is essential for optimizing strategies and enhancing team performance. Preprocessing steps included data cleaning, feature engineering, and visualization of key features such as goals, shots, and attacking attempts. Four clusters were identified using the Elbow method, representing teams with varying levels of attacking and defensive capabilities. Evaluation of the clustering results was conducted using Davies-Bouldin (score: 0.47), Calinski-Harabasz (score: 275.89), and Silhouette (score: 0.53) metrics, indicating moderate clustering quality. The findings suggest that EPL teams tend to be attack-oriented, while defensive strength varies across clusters. Limitations in the dataset, such as the number of observations and features, impacted the analysis, and future studies may benefit from incorporating additional features and advanced dimensionality reduction techniques.